1947
DOI: 10.1172/jci101821
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Action of Clostridium Welchii (Type A) Toxins in Dogs 123

Abstract: Recent work reported from this laboratory (1 to 7) has shown that clostridia grow and produce toxins readily in anoxic muscle in zivo, and that they are readily introduced into dog muscles during the course of traumatizing procedures. Moreover, our previous experiments have suggested that these and perhaps other bacteria may be responsible for a toxic factor contributing to shock in traumatizing wounds. Since clostridia are known to be frequent contaminants of war wounds (8, 9) it appeared desirable to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1947
1947
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…welchii toxic filtrates (14) have demonstrated that the dosage, rate, and route of administration of the toxins determine the type of effects on dogs. The same considerations apply to the present studies on Cl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…welchii toxic filtrates (14) have demonstrated that the dosage, rate, and route of administration of the toxins determine the type of effects on dogs. The same considerations apply to the present studies on Cl.…”
Section: Discussionmentioning
confidence: 99%
“…oedematiens (Novyi) The methods used in this study have been described previously (14), with the following exceptions: liver function was tested by the bromsulfalein excretion method; and kidney function was tested by phenolsulfonphthalein excretion.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the information presently available we may en vision a qualified picture of the mechanism of gas gangrene infec (180), and collagenase may add its characteris tic activity to create the pulped muscle appearance generally seen in gangrene. This evidence is most complete for C. perfringens, but probably applies as well to those other clostridia which are able to initiate gas gangrene infections.…”
Section: Acquired Immunity Against Infectious Disease 253mentioning
confidence: 99%
“…Zamecnik, Nathanson & Aub have described these for C. perfringens(180) and for C. novyi(181), and Pasternack & Bengston (182) for C. septicum. C. perfringens toxic filtrate pro duces gross intravascular hemolysis and fall in blood pressure ;C. novyi toxin acts principally upon the peripheral vascular system; and with C. septicum filtrate cardiotoxic and nephrotoxic proper ties predominate.Some information regarding successful immunization against gas gangrene by the use of toxoids has been available for years,but a great deal was added during the latter years of World War Annu.…”
mentioning
confidence: 99%